2001
DOI: 10.3758/bf03192811
|View full text |Cite
|
Sign up to set email alerts
|

Blocking in landmark-based search in honeybees

Abstract: Two experiments tested blocking in landmark-based search in honeybees. Honeybees in the experimental group were trained in Phase 1 with a single landmark in a constant spatial relation to the target (sugar water). In the compound training second phase, the landmark used in Phase 1 (blocking landmark) and a new landmark (blocked landmark) were presented at constant spatial relations to the target. The blocking and blocked landmarks differed from each other in color and position, and the blocking landmark retain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 45 publications
(67 reference statements)
1
20
1
Order By: Relevance
“…Comparative psychology has revealed broad regularities in the general principles of learning across invertebrate and vertebrate taxa (Logue 1988;Domjan 1998) and across spatial and temporal domains (Cheng & Spetch 2001). The general principles that apply to learning in bees, pigeons and rats are likely to apply to fishes also.…”
mentioning
confidence: 99%
“…Comparative psychology has revealed broad regularities in the general principles of learning across invertebrate and vertebrate taxa (Logue 1988;Domjan 1998) and across spatial and temporal domains (Cheng & Spetch 2001). The general principles that apply to learning in bees, pigeons and rats are likely to apply to fishes also.…”
mentioning
confidence: 99%
“…In experiments in which the same experimental paradigm has been used (e.g., Sánchez-Moreno, Rodrigo, Chamizo, & Mackintosh, 1999), evidence has been found that an auditory cue can overshadow a visual landmark cue (and that the landmark overshadows the auditory cue). Blocking among spatial landmarks has also been reported in honeybees (Cheng & Spetch, 2001), and overshadowinghas been reported among spatial cues in a computer-display-basedsearch task in pigeons and humans (Spetch, 1995).…”
mentioning
confidence: 99%
“…This failure could represent a form of blocking in which a previously learned association prevents a new association from forming (Kamin, 1969;Cheng and Spetch, 2001). In the experiments by Towne et al (Towne et al, 2005), the recipient landscape closely resembled the bees' natal landscape, and several features of the food source at the recipient site -the design of the feeder, the scent of the food, the landmarks en route to the feeder, the feeder's distance from the hive, the local landmarks at the feeder and the times of day at which food was available -were all familiar.…”
Section: Introductionmentioning
confidence: 99%